The SAGE handbook of curriculum, pedagogy and assessment - Wyse, Dominic 1964-; Hayward, Louise; Pandya, Jessica Zacher (SAGE, 2016)
The research and debates surrounding curriculum, pedagogy and assessment are ever-growing and are of constant importance around the globe. With two volumes - containing chapters from highly respected researchers, whose work has been critical to understanding and building expertise in the field - this handbook focuses on examining how curriculum is treated and developed, and its impact on pedagogy and assessment worldwide
Keywords: Education -- Curricula; Curriculum-based assessment; Curriculum; Pädagogik; Aufsatzsammlung